IEEE INFOCOM 2018 - IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS) 2018
DOI: 10.1109/infcomw.2018.8406872
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of performance in integrated access and backhaul networks

Abstract: Wireless backhaul allows densification of mobile networks without incurring additional fiber deployment cost. This, in turn, leads to high spatial reuse, which is a significant tool to meet increasing wireless demand in 5G networks. Integrated access and backhaul (IAB), where access and backhaul network share the same standard wireless technology (e.g. 5G new radio (NR) standard), allows interoperability among different IAB manufacturers and flexible operation between access and backhaul. This paper investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Resource allocation-related approaches and results can be found in, e.g., Islam et al (2017Islam et al ( , 2018, Li et al (2017), Saha et al (2018), Dhillon (2019), andLiu et al (2020). In Saha and Dhillon (2019), the authors first focus on a stochastic geometry-based model for analytically characterizing the performance of IAB networks, such as the downlink rate coverage probability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Resource allocation-related approaches and results can be found in, e.g., Islam et al (2017Islam et al ( , 2018, Li et al (2017), Saha et al (2018), Dhillon (2019), andLiu et al (2020). In Saha and Dhillon (2019), the authors first focus on a stochastic geometry-based model for analytically characterizing the performance of IAB networks, such as the downlink rate coverage probability.…”
Section: Related Workmentioning
confidence: 99%
“…Based on simulation results, it is concluded that IAB can significantly reduce the fiber drop deployment cost of the network compared to fixed access backhaul network. In Islam et al (2018), a joint resource allocation and relay selection in a multi-hop IAB network is investigated to maximize the geometric mean of UE rates and with the aim of demonstrating the advantages of IAB networks over purely access networks. Without providing any algorithmic details, the proposed method focuses on an optimal mesh solution by maximizing a defined objective function.…”
Section: Related Workmentioning
confidence: 99%
“…A distributed approach to calculate new IAB topologies was presented in [21], where IAB-nodes selected parent nodes based on link signal strength and on the number of hops needed to reach an IAB-donor. In addition, authors in [22] considered existing resource sharing between IAB links when forming backhaul topologies.…”
Section: Related Workmentioning
confidence: 99%
“…We then analyse traffic demand in the access network, load balancing across IAB-donors, the maximum number of hops, and the selected routes' path length to optimally select the association between IAB-donors and IAB-nodes, and the path connecting them. The authors in [10] investigate joint resource allocation and relay selection in a multi-hop IAB network to maximise the geometric mean of UE rates. They compare different optimisation variants, considering Reference Signal Receive Power (RSRP)-based spanning tree and mesh IAB network, including the impact of load-balancing in the access network.…”
Section: A Related Work and Our Contributionmentioning
confidence: 99%
“…They compare different optimisation variants, considering Reference Signal Receive Power (RSRP)-based spanning tree and mesh IAB network, including the impact of load-balancing in the access network. Minimising the number of donors is a common objective in [10] and our work. However, the authors there incorporate a constraint on the UE demand in the access network, while this work includes the constraint on the maximum number of hops, informed by delay considerations for eMBB traffic.…”
Section: A Related Work and Our Contributionmentioning
confidence: 99%